Enriching the quality of cross‐cultural instrument development through cognitive interviewing: Implications for nursing research. Issue 2 (13th November 2019) - Jang, Min Kyeong; Kim, Sue; Collins, Eileen G.; Quinn, Lauretta T.; Park, Chang G.; Ferrans, Carol E.
Abstract: Aim: During cross‐cultural instrument development, a gap commonly exists between the intended meaning of questionnaire items and the extent to which the participant understands that meaning. Because cognitive interviewing can provide such a powerful means for ensuring an accurate interpretation of items, the purpose of this report is to provide a practical guide to encourage its use in nursing research. Methods: This report provides in‐depth information describing: (a) advantages of cognitive interviewing, particularly for cross‐cultural instrument development; (b) specific problems it can identify and solve; (c) strategies for performing cognitive interviews, including the four‐step model of the question‐and‐answer process; (d) practical guidance for conducting successful cognitive interviews. Results: To achieve linguistic validity as well as cultural relevance, a variety of factors need to be considered in addition to language, such as cultural interpretations, attitudes, and values. Examples of health‐related studies are presented, demonstrating the advantages of cognitive interviewing for instrument development and cross‐cultural research. These examples show how cognitive interviewing can be productively used to verify question clarity, patient comprehension, and patients' ease of response and judgment while also helping to establish content validity based on patients' perspectives. Conclusions: Cognitive interviewing can help nurse researchers discover potential instrument flaws and correct them in advance, subsequently avoiding collection of inaccurate data. Thus, cognitive interviewing should be considered an effective pretesting method for development of accurate instruments, particularly in cross‐cultural nursing research.